2014
DOI: 10.4314/ejhs.v24i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Bone Cyst of Idiopathic Origin? A Report of Two Cases

Abstract: BackgroundTraumatic bone cyst (TBC) is an uncommon non-epithelial lined cavity of the jaws. Traumatic bone cysts have been reported in the literature under a variety of names: solitary bone cyst, haemorrhagic bone cyst, extravasation cyst and simple bone cyst. The multitude of names applied to this lesion implies the lack of understanding of the true aetiology and pathogenesis. However, the term “traumatic bone cyst” is the most widely used name today (1).Case DetailsA 15 years old male patient presented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The surrounding bone is destroyed by enzymatic activity and as a result, the bone cavity enlarges, stimulated by poor venous drainage. 10,16 Nevertheless, unusually large TBCs with an aggresive course have been rarely reported. 12 While panoramic radiography is usually sufficient for diagnosing a traumatic bone cyst.…”
Section: Discussionmentioning
confidence: 99%
“…The surrounding bone is destroyed by enzymatic activity and as a result, the bone cavity enlarges, stimulated by poor venous drainage. 10,16 Nevertheless, unusually large TBCs with an aggresive course have been rarely reported. 12 While panoramic radiography is usually sufficient for diagnosing a traumatic bone cyst.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Idiopathic bone cavities are generally detected in patients in the second and third decades of life, although they can also be found in older age groups. 5 The mandibular body is the most frequent site of idiopathic bone cavity; PRP and healing in the idiopathic bone cavity 3 however, cases involving the mandibular symphysis, ramus, condyle, and even the anterior maxilla have been reported. 6 The definite diagnosis of idiopathic bone cavity is achieved by surgical intervention, whereby an empty bone cavity without epithelial lining is visualized.…”
Section: Discussionmentioning
confidence: 99%
“…12 The recurrence rate has been reported to be greater than 20%. 5 Precious et al showed that the injection of autologous blood into the bony cavity of an idiopathic bone cavity that had not responded effectively to surgical curettage, was followed by rapid resolution of the lesion. 8 It is obvious that osteoblasts can originate from progenitor cells within blood vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A traumatic bone cyst is a rare non-epithelial-lined cyst found in the mandibular bone. The true etiology is unclear, but the lesion is called a traumatic cyst [32]. Almost all bone cysts found in long-term or older hemodialysis patients are associated with beta 2-microglobulin amyloid deposition.…”
Section: Bone Cystmentioning
confidence: 99%